Home Environmental Factors and the Incidence of Acute Respiratory Infections in Toddlers: A Case Study in the Tanggetada and Watubangga Community Health Centers - Yusuf Wawan Artist Sulaiman; Erwin Azizi Jayadipraja; Wa Ode Nova Noviyanti Rahcman (Waluya The International Science of Health Journal, 2026)
Introduction: The initial survey conducted on 10 people in the Tanggetada Community Health Center Working Area stated that of the 10 people, 3 of their children suffered from ARI due to poor ventilation, exposure to cigarette smoke, and 3 people said the cause was dense housing and 3 people said their children had not been immunized. Based on this, the researcher wanted to examine the relationship between smoking habits in the home and cooking fuel with ARI in the Regional Technical Implementation Unit Working area of the Tanggetada Watubangga Community Health Center, Kolaka Regency, Southeast Sulawesi Province. Method: This quantitative research, using a cross-sectional study approach, was conducted in the districts of Southeast Sulawesi Province. The population was 822 toddlers and the sample size was 90, determined using the Slovin formula. Result: The chi square statistical test on smoking habits with a 95% confidence level (α = 0.05) shows that the value indicates that the X2count value = 7.813 > X2table value = 3.841 and on Fuel with a 95% confidence level (α = 0.05) shows that the value indicates that the X2count value = 10.944 > X2table value = 3.841, which means there is a relationship between cooking fuel and the incidence of ARI.  Conclusion: There is a weak relationship between smoking habits and fuel and the incidence of ARI in the working areas of Tanggetada Health Center and Watubangga Health Center.